Preserving the cultural bond towards strengthening Sino-Malaysian friendship - Ku, Boon Dar (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
This paper is an attempt to trace the history of traditional friendship between China and Malaysia which had been established since the Han Dynasty. The ties between both countries were further strengthened in the 15th century with the establishment of diplomatic relation between the Ming Dynasty and the Malacca Sultanate. The paper also discusses the diplomatic ties between China and Malaysia which was officially reconciled in 1974 during the second Malaysia Prime Minister, Tun Abdul Razak bin Hussein’s visit to China. This bilateral relationship has continued to develop and gained significance with China’s ‘One Belt One Road’ initiative in 2013, which was inspired by China’s president, Xi Jinping. The paper describes the relationship between the two great empires (China and the Malay world), which carries a special significance in the context of the interaction of civilizations. This interaction does not only revolve around the issues of trade, investment and tourism alone but its significance is also visible in various socio-cultural issues especially the development of the Malay language in China.